2013
DOI: 10.1016/j.cub.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Eye Movements Compensate for Nonhomogeneous Vision within the Fovea

Abstract: Summary Humans rely on the fovea, the small region of the retina where receptors are most densely packed, for seeing fine spatial detail. Outside the fovea, it is well established that a variety of visual functions progressively decline with eccentricity [1–5]. In contrast, little is known about how vision varies within the central fovea, as incessant microscopic eye movements prevent isolation of adjacent foveal locations [6–8]. Using a new method for restricting visual stimulation to a selected retinal regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 36 publications
12
153
1
Order By: Relevance
“…In contrast to many other studies, we did not demonstrate a sustained effect of a cognitive state on microsaccade rates (Cui et al 2009;Poletti et al 2013;Steinman et al 1967; or an influence of microsaccades on perceptual performance (Deubel and Eisner 1986;Martinez-Conde et al 2006). Rather, we showed that trial-by-trial variations in perception are linked (within 1/10 of a second after the stimulus onset) to these involuntary eye movements.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast to many other studies, we did not demonstrate a sustained effect of a cognitive state on microsaccade rates (Cui et al 2009;Poletti et al 2013;Steinman et al 1967; or an influence of microsaccades on perceptual performance (Deubel and Eisner 1986;Martinez-Conde et al 2006). Rather, we showed that trial-by-trial variations in perception are linked (within 1/10 of a second after the stimulus onset) to these involuntary eye movements.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, physically weak or adapted stimuli are detected relatively infrequently, but when they are detected they cause strong oculomotor freezing. Similarly, some researchers have posited that conscious detection is an all-or-none phenomenon (Dehaene and Changeux 2011;Dehaene et al 2003;Quiroga et al 2008). We argue that across-trial aggregate measures of perceptual sensitivity (d=) and the oculomotor response show similar effects of stimulus parameters (such as contrast, as shown in our experiment 1 and by Bonneh et al 2015 andScholes at al.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It seems that microsaccades fulfill the same purpose as large saccades, precisely shifting gaze to the most relevant locations to achieve the goal of a task (Kowler and Collewijn, 2010). This claim is further supported by the finding that visual sensitivity is not homogenous across the fovea and microsaccades bring the stimulus onto the preferred retinal locus of fixation (Poletti et al, 2013). Moreover, an excess of microsaccades is observed during inspection of informative scene regions, suggesting a role of microsaccades in the sampling of visual information (McCamy et al, 2014b).…”
Section: Introductionsupporting
confidence: 56%
“…In particular, it was shown that not only these movements prevent retinal image fatigue and visual fading, but play also a crucial role in controlling the fixation position (Engbert and Kliegl 2004). Experiments (see, e.g., Donner and Hemilä 2007;Rucci et al 2007;McCamy et al 2012;Poletti et al 2013) reveal that the retinal responses caused by microsaccadic movements reduce aliasing effects in the peripheral retina, lead to improved spatiotemporal accuracy of the neural responses, and provide additional information that allows resolving fine spatial details out of optically blurred images.…”
Section: Narrow Visual Field and Saccadic Eye Movementsmentioning
confidence: 98%